CONTACT METAMORPHISM OF QUARTZ VEINS IN THE NORTHERN PORTION OF THE ALLAKH-YUN' GROUP OF GOLD-BEARING DEPOSITS, YAKUTIA, RUSSIA: EVIDENCE FROM FLUID INCLUSIONS - Gibsher N.A.; Tomilenko A.A. (My University, 2003)
Fluid inclusions were studied in quartz of concordant and discordant quartz veins from the gold-bearing deposits of the Allakh-Yun' group, Yakutia. The study area consists of four quartz-veined zones located at different distances from the Tarbagannakh granitoid massif: (I) Khotun zone, 20-25 km from the massif; (II) Bular zone, 10-15 km; (III) Khochulukan zone, 5-7 km; and (IV) Mugun zone, in the outer contact of the massif. With decreasing distance from the Tarbagannakh massif from I to IV zones, the total gas content in quartz decreases from 0.08 to 0.02 wt %, while CO2 proportion in fluid increases, on average, from 10 to 40 mol %. The aqueous and aqueous-carbon dioxide inclusions in the concordant quartz veins from I and II zones have Thom = 230-290°C and a salinity of 15-20 wt % NaCl equiv. Those in the discordant veins have Thom = 350-400°C and a salinity of 3-8 wt % NaCI equiv. Similar inclusions in the concordant and discordant veins from III and IV zones are close in homogenization temperature and salinity (120-360°C, 2-9 wt % NaCl equiv.). Carbonaceous matter crystallinity and quartz granulation increase toward the intrusion. The fluid inclusion data and Raman spectroscopy of the carbonaceous matter indicate that the majority of the quartz veins of the Allakh-Yun' group of deposits formed during regional greenschist metamorphism. Later, quartz veins experienced thermal metamorphism caused by the emplacement of the Tarbagannakh granitoid intrusion.